Digital Game-Based Heritage Education: Analyzing the Potential of Heritage-Based Video Games - Daniel Camuñas-García; María Pilar Cáceres-Reche; María de la Encarnación Cambil-Hernández; Manuel Enrique Lorenzo-Martín (MDPI AG, 2024)
Video games have emerged as a promising tool for enhancing engagement with cultural heritage. However, there is limited knowledge about how existing games can effectively fulfill this role. This study compiled and analyzed 100 video games based on cultural heritage by adapting an existing framework that includes 10 game attributes for a comparative statistical analysis of the games' engagement features. These features include narrative-driven gameplay, information capsules, task-driven learning, ease of play, identity-driven content, open-world exploration, people-centered perspectives, meaningfulness, simulation, and verisimilitude. The analysis revealed that while the majority of games adhered to most of the recommended attributes, features such as task-driven learning, open-world exploration, and simulation were either uncommon or rare. These findings highlight a significant opportunity to develop games that incorporate these underrepresented features, thereby providing more immersive and engaging experiences in heritage education. Furthermore, the study offers a systematic overview of existing games that represent cultural heritage, serving as a valuable resource for developers, designers, and educators in this field.